The Taliban's Media Strategy in Changing Global Public Perception: After the Occupation of Afghanistan in 2021 - Amalia, Nadhifah (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2026)
This study aims to analyze the Taliban's media strategy in shaping its global image after the occupation of Afghanistan in 2021. Using qualitative descriptive research methods and the war of ideas theoretical framework, this descriptive-qualitative study examines how the Taliban utilizes social media, press conferences, and engagement with international media to construct a positive narrative and gain global legitimacy. The results show that the Taliban uses narrative warfare, public diplomacy, and digital propaganda as instruments of soft power. These strategies have been relatively successful in expanding legitimacy through foreign media coverage, influencer engagement, and tourism promotion. However, there are still limitations related to opposition and official recognition from other countries, caused by inconsistent policies on women's and minority rights. These findings confirm that the success of the Taliban's media strategy is partial, as internal structural factors and obstacles to global legitimacy remain major challenges.